2021
DOI: 10.1002/hpm.3121
|View full text |Cite
|
Sign up to set email alerts
|

Strategic assessment of mental health and suicide amid COVID‐19 pandemic in Bangladesh

Abstract: The purpose of this study is to explore how the coronavirus disease 2019 pandemic has affected the mental health of our society in Bangladesh as a thorough assessment of mental health is salient during this pandemic crisis. The study seeks to ensure that their unheard voices are reached to both national and international academic discourse, which has so far been uninhabited. It adopted qualitative interpretative methods of social research through content analysis. The study found that the pandemic did not affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…To the best of the author's knowledge, this is the rst systematic review on common mental health problems during the COVID-19 pandemic in Bangladesh (43,44), which has potential implications for mental health policymaking and practice. It is anticipated that the ndings presented herein can be implemented for (i) developing cost-effective mental health strategies, (ii) prioritizing and integrating mental health in existing healthcare systems, (iii) improving access to information and mental health resources, (iv) addressing mental health disparities across different cohorts, (v) mobilizing social and community resources and organizations, (vi) strengthening mental health systems for the forthcoming public health emergencies etc.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of the author's knowledge, this is the rst systematic review on common mental health problems during the COVID-19 pandemic in Bangladesh (43,44), which has potential implications for mental health policymaking and practice. It is anticipated that the ndings presented herein can be implemented for (i) developing cost-effective mental health strategies, (ii) prioritizing and integrating mental health in existing healthcare systems, (iii) improving access to information and mental health resources, (iv) addressing mental health disparities across different cohorts, (v) mobilizing social and community resources and organizations, (vi) strengthening mental health systems for the forthcoming public health emergencies etc.…”
Section: Discussionmentioning
confidence: 99%
“…The public health crisis applies to people of all ages across the globe. For developing countries including Bangladesh, the COVID-19 pandemic is a humanitarian crisis with a public health dimension ( Ahmed & Sifat, 2021 ). In December 2019, the virus, first detected in Wuhan, China, affected 215 nations, regions, or territories with 230,104 deaths and 3,272,202 positive cases worldwide, as of May 03, 2020 ( Ferdous et al., 2020 ; M. S. Islam et al., 2020 ; World Health Organization, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence showed that the prevalence of anxiety among physicians in Bangladesh during COVID-19 outbreak was high in comparison to previous epidemics ( Khatun et al., 2021 ), In Bangladesh, frontline fighters are anticipated to be most vulnerable to these sufferings mainly because of the crowds of peoples, shortage of personal protective equipment. Moreover, a recent report claimed patients' suicide occurrence because of treatment negligence by the healthcare professionals in Bangladesh ( Ahmed & Sifat, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…10 The poorest who survive on daily wage labor show that economic mortality overshadows health mortality. 3,11 In this pandemic, day-wage earners have struggled the most, but hijra people do not survive on a daily wage as they do get into jobs in the mainstream industries owing to their outdoor activities and lifestyle. 11 Hijra groups have been accused as being carriers of the virus.…”
Section: Transgender Person's Need For National Assistancementioning
confidence: 99%
“…3,11 In this pandemic, day-wage earners have struggled the most, but hijra people do not survive on a daily wage as they do get into jobs in the mainstream industries owing to their outdoor activities and lifestyle. 11 Hijra groups have been accused as being carriers of the virus. Many hijra people are shunned by local elites and mosques and are left out of conventional support for relief (https://www.dhakatribune.com).…”
Section: Transgender Person's Need For National Assistancementioning
confidence: 99%